PEMBERDAYAAN KELOMPOK USAHA TENTENG KACANG TANAH - Muhammad Iksan; Suparni Sampetan (BERKEMAJUAN : JURNAL PENGABDIAN PADA MASYARAKAT, 2022)
Tenteng Kacang Tanah is one of traditional snacks from Palopo. This food is very popular because of its delicious taste. However, day by day, this snack become rare because of the invasion of modern snacks that are produced massively by bigger and stronger company. Based on that consideration, an attempt to conserve that local snack was initiated. The inadequacy of capital and tools of production became a part of problems of the home industry businessmen to develop their business. The producer of Tenteng Kacang Tanah were still difficult to produce their product in a large amount. This was caused by the inadequacy of the capital to buy the materials of Tenteng Kacang Tanah as well as the inadequacy of production equipments such as printer and package sealer. Therefore, this IbM program was conducted to assist the group of Tenteng Kacang Tanah producers in terms of providing business capital and also the production equipments. By the assistance of production equipments, it was expected to be able to shorten the production duration and the production cost as well as creating good quality and competitive products. While by the assitance of business capital to both program partner, it was expected to be able to encourage the production process to be more productive in a larger capacity and to encourage the program partner to administer a professional business management. Generally, this IbM program had been successfully to increase the quantity and the quality of the products and directly impact the life prosperity of the producer of Tenteng Kacang Tanah.